Xylopioxyde and other bioactive kaurane-diterpenes from Xylopia aethiopica Dunal (Annonaceae) - Désiré SOH, Ernestine NKWENGOUA,Igor NGANTCHOU & , Barthélemy NYASSE, Colette DENIER, Véronique HANNAERT, Kamel H. SHAKER and Bernd SCHNEIDER (Journal of Applied Pharmaceutical Science, 2013)
A new cytotoxic ent-kaurane-type diterpene named xylopioxyde (16,17-epoxy-15-oxo-ent-kauran-19-oic acid) has been isolated from the fruits of Xylopia aethiopica Dunal (Annonaceae) together with three known compounds, namely 15α-acetoxy-ent-kaur-16-en-19 oic acid (xylopic acid), 15-oxo-ent-kaur-16-en-19-oic acid and ent-kaur-16-en-19-oic acid. Xylopic acid, obtained in a good amount, has been successively converted in moderate to good yields into 15-hydroxy-ent-kaur-16-en-19-oic acid, 15-oxo-ent-kaur-16-en-19-oic acid and two new selective trypanocidal stereoisomers of 15-acetoxy-16,17-ent-epoxy-kauran-19-oic acid, respectively. All the compounds except the synthetic epoxides displayed cytotoxic effects on the mammalian fibroblast cell line MRC-5 as well as inhibitory effects on the growth of the bloodstream forms of Trypanosoma brucei brucei cells (strain 241).
Keywords: Cytoxic effets, Trypanosoma brucei brucei, ent-kauranes, epoxidation, Xylopia aethiopica Dunal.